2014
DOI: 10.1158/1535-7163.mct-13-0629
|View full text |Cite
|
Sign up to set email alerts
|

MCL-1 Degradation Mediated by JNK Activation via MEKK1/TAK1-MKK4 Contributes to Anticancer Activity of New Tubulin Inhibitor MT189

Abstract: Colchicine site-targeted tubulin inhibitors are a promising type of anticancer drugs. MT189 is a new derivative of MT119, a previously reported colchicine site-binding antitubulin agent. In this study, MT189 was demonstrated to retain the property of MT119 in disrupting microtubulin via binding to the colchicine site, causing mitotic arrest and inducing apoptosis, and to display 8.7-fold enhanced proliferative inhibition in a panel of cancer cells. MT189 was shown to elicit in vivo anticancer effects on MDA-MB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Then the cells were subjected to the Cell Counting Kit 8 (CCK8) assays (Chinese hamster cells, Ewing sarcoma cells, HCC1937 and MDA-MB-436 cells) or by Sulforhodamine B (SRB) assays (all the other cells) as described previously [18, 19]. The inhibition rate (%) was calculated as: [1-(A450 treated /A450 control )] × 100%.…”
Section: Methodsmentioning
confidence: 99%
“…Then the cells were subjected to the Cell Counting Kit 8 (CCK8) assays (Chinese hamster cells, Ewing sarcoma cells, HCC1937 and MDA-MB-436 cells) or by Sulforhodamine B (SRB) assays (all the other cells) as described previously [18, 19]. The inhibition rate (%) was calculated as: [1-(A450 treated /A450 control )] × 100%.…”
Section: Methodsmentioning
confidence: 99%
“…The decreased Mcl-1 protein levels were reversed by a proteasome inhibitor, supporting the important role of the proteasome in regulating Mcl-1 levels in APAPtreated hepatocytes. Finally, Mcl-1 degradation has also been shown to be induced by JNK phosphorylation in HeLa cells (55). Parkin KO mice had reduced JNK activation, which may be linked to their increased Mcl-1 expression.…”
Section: Mcl-1 Expression Was Differentially Regulated In Parkin Ko Omentioning
confidence: 96%
“…SK-OV-3 cells were treated with 1 mmol/L triptolide for the indicated times, and cells were treated as described previously (10).…”
Section: Immunoprecipitationmentioning
confidence: 99%
“…We reported that specific compounds can directly kill MDR tumor cells without affecting the function of P-gp, such as the natural products salvicine (3,4), pseudolaric acid B (5, 6), methyl spongoate (7), tanshinone I (2,8), and synthetic small molecules YCH337 (9) and MT series (10)(11)(12). Among them, the MDRovercoming activities of natural products were associated with the regulation of certain transcription factors.…”
Section: Introductionmentioning
confidence: 99%